2018
DOI: 10.1016/j.neuroscience.2017.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Pregnane X Receptor Deletion Modifies Recognition Memory and Electroencephalographic Activity

Abstract: Nuclear receptors (NR) are emerging as key players in the central nervous system (CNS) with reported implications in physiological and pathophysiological conditions. While a number of NR has been studied, it is unknown whether invalidation of the pregnane xenobiotic receptor (PXR, NR1I2) corresponds to neurological modifications in the adult brain. PXR−/− C57BL/6 J and wild-type mice were used to investigate: (i) recognition memory, motor coordination, and anxiety-like behaviors; (ii) longitudinal video-electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…sleep/immobility, and avoiding all motion artifacts. Periodogram Power Bands (Neuroscore) was calculated for all EEG and the relative abundance of each 0.5 Hz increment (0.5-80 Hz) was quantified (Boussadia et al, 2018(Boussadia et al, , 2016Ichkova et al, 2020). As we routinely perform and we previously described (Ichkova et al 2020, Zub et al 2019, spike or seizure analysis was executed as follow: 1) setting a threshold for spike detection of 2.5 x times the standard deviation of the baseline; 2) minimum and maximum spike duration (1 and 100 ms); 3) minimum train-spike duration 5s with a minimum number of spikes of n= 5 (at least 1Hz).…”
Section: Freely Moving Telemetry Video-electroencephalographymentioning
confidence: 99%
“…sleep/immobility, and avoiding all motion artifacts. Periodogram Power Bands (Neuroscore) was calculated for all EEG and the relative abundance of each 0.5 Hz increment (0.5-80 Hz) was quantified (Boussadia et al, 2018(Boussadia et al, , 2016Ichkova et al, 2020). As we routinely perform and we previously described (Ichkova et al 2020, Zub et al 2019, spike or seizure analysis was executed as follow: 1) setting a threshold for spike detection of 2.5 x times the standard deviation of the baseline; 2) minimum and maximum spike duration (1 and 100 ms); 3) minimum train-spike duration 5s with a minimum number of spikes of n= 5 (at least 1Hz).…”
Section: Freely Moving Telemetry Video-electroencephalographymentioning
confidence: 99%
“…Important enough, GA shows much lower cytotoxicity compared with δ-T3, thus allowing treatments with much higher doses; furthermore, the more hydrophilic properties of GA may favor compound permeability through the blood-brain barrier. The fact that GA is available to the mouse brain and, along with PPARγ, it up-regulates PXR expression of this tissue, suggests other pharmacological applications, including anxiety-like behavior and recognition memory ( 39 ), and blood barrier function modulation ( 40 ) that are all PXR-dependent processes. Other therapeutic effects of GA could be anticipated in lipid and metabolic disorders associated with higher demand of ApoE activity or unfavorable APOE haplotypes ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have proposed that alterations in NR1I2 and NR1I3 function could impair the expression of tight junction proteins at the BBB since deletion of NR1I2 and NR1I3 in rats leads to reduced expression of zonula occuldens-1 protein in isolated brain microvessels, with no changes in claudin-5 expression reported (Boussadia et al, 2016;Boussadia et al, 2018). Although this is the only evidence available to date at brain level, it is supported by a previous study that demonstrated the relationship between NR1I2 and expression of TJ proteins in the intestine, in which NR1I2 (−/−) mice exhibited higher intestinal permeability (Venkatesh et al, 2014).…”
Section: Humanmentioning
confidence: 99%
“…More recently, studies report that deletion of NR1I3 and NR1I2 in rodents severely impairs recognition memory and increases development of anxiety-like behaviours (Boussadia et al, 2016;Boussadia et al, 2018). Furthermore, both studies associated the absence of these NRs with alterations in the electroencephalographic signatures during sleep/awake periods.…”
Section: Nr1i3 (Car) and Nr1i2 (Pxr): Roles In Behaviour And Other mentioning
confidence: 99%